Analysing student's experience of using a digital notebook in learning physics / Easter Joseph and Zuraini Hanim Zaini - Joseph, Easter; Zaini, Zuraini Hanim (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Recent technological developments have led to the prominence of online education as an alternative to traditional classroom teaching. Due to the current health crisis happening around the world, online teaching and learning have been implemented at a national scale among students and academic staff, at all educational levels. This research paper aims to demonstrate the student's learning experience by using digital notebook, particularly Microsoft One note in monitoring and managing their online learning in Physics subject. As some students encountered difficulties to accommodate the online teaching and new learning environment especially in understanding Physics course, employing a digital notebook is essential to ensure all students acquire systematic information and able to monitor their performance. A total of 30 Foundation students were required to use this digital notebook for 12 weeks (one semester) as an interactive platform to share, collaborate, and discuss the coursework efficiently and engagingly. Students' reflections through an online survey was conducted and analyzed by using Co-occurrences Analysis. The result of the analysis revealed that the students appreciate the usage of this platform as it is convenient, effective, informative, and systematic. Hence, this digital notebook appears as an effective tool to encounter the challenges in terms of students' collaboration, flexibility, accessibility, and interactivity.